Dripless: A smart household water monitoring system - Islam Abdelfattah; Mohamed F. Abdelkader; Atef Ghuniem (International Telecommunications Society (ITS), 2019)
Egypt is facing a water scarcity challenge in the upcoming years, making rationalizing household water consumption an issue of national priority. Dripless is a residential wireless water monitoring and control system that offers leak detection and prevention. It uses a smartphone dashboard to provide users with the ability to monitor and control their household water remotely. This paper introduces the dripless system, features, components, and challenges.
Keywords: 330; IOT; Water Saving; Water consumption monitoring; Smart Cities